The Impact of Intraoperative Frozen Section on Resection Margin Status and Survival of Patients Underwent Pancreatoduodenectomy for Distal Cholangiocarcinoma - Chen, Zhiqiang; Yu, Bingran; Bai, Jiaping; Li, Qiong; Xu, Bowen; Dong, Zhaoru; Zhi, Xuting; Li, Tao (Frontiers in Oncology, 2021)
Background Intraoperative frozen section (FS) is broadly used during pancreaticoduodenectomy (PD) to ensure a negative margin status, but its survival benefits on obtaining a secondary R0 resection for distal cholangiocarcinoma (dCCA) is controversial and unclear. Methods Clinical data of 107 patients who underwent PD for dCCA was retrospectively collected and divided into different groups based on use of FS (FS and non-FS groups) and status of resection margin (pR0, sR0 and R1 groups), and clinical parameters and survival of patients were compared and analyzed accordingly. Results There were 50 patients in FS group with a median survival of 28 months, 57 patients in non-FS group with a median survival of 27 months. There was no statistical difference between the 2 groups with Kaplan-Meier survival analysis (P=0.347). There were 98 patients in R0 group (88 in pR0 and 10 in sR0) and 9 patients in R1 group, with a median survival of 29 months and 22 months respectively, which showed a better survival in R0 group than in R1 group (P=0.006). Survival analyses between subgroups revealed difference between pR0 and R1 group (P=0.005), while no statistical difference concerning pR0 vs. sR0 (P=0.211) and sR0 vs. R1 groups (P=0.262). Multivariate Cox regression analysis revealed resection margin status, pre-operative biliary drainage and lymph node invasion to be independent prognostic factors for dCCA patients. Conclusions Intraoperative FS should be recommended as it significantly increased the rate of R0 resection, which was positively related to a better survival. A primary R0 resection should also be encouraged and if not, a secondary R0 could be considered at the discretion of surgeons as it showed similar survival with primary R0 resection.